Stress Models of the Annual Hydrospheric, Atmospheric, Thermal, and Tidal Loading Cycles on California Faults: Perturbation of Background Stress and Changes in Seismicity. Issue 12 (26th December 2017) - Johnson, Christopher W.; Fu, Yuning; Bürgmann, Roland
Abstract: Stresses in the lithosphere arise from multiple natural loading sources that include both surface and body forces. The largest surface loads include near‐surface water storage, snow and ice, atmosphere pressure, ocean loading, and temperature changes. The solid Earth also deforms from celestial body interactions and variations in Earth's rotation. We model the seasonal stress changes in California from 2006 through 2014 for seven different loading sources with annual periods to produce an aggregate stressing history for faults in the study area. Our modeling shows that the annual water loading, atmosphere, temperature, and Earth pole tides are the largest loading sources and should each be evaluated to fully describe seasonal stress changes. In California we find that the hydrological loads are the largest source of seasonal stresses. We explore the seasonal stresses with respect to the background principal stress orientation constrained with regional focal mechanisms and analyze the modulation of seismicity. Our results do not suggest a resolvable seasonal variation for the ambient stress orientation in the shallow crust. When projecting the seasonal stresses into the background stress orientation we find that the timing of microseismicity modestly increases from an ~8 kPa seasonal mean‐normal‐stress perturbation. The results suggest that faults in California are optimally oriented with the background stress field and respond to subsurface pressure changes, possibly due to processes we have not considered in this study. At any time a population of faults are near failure as evident from earthquakes triggered by these slight seasonal stress perturbations. Key Points: Mechanical models are developed to quantify stress changes for the regional fault geometry induced by seven sources of annual loading Annual hydrospheric loading in California produces the largest Coulomb stress changes of 0.5–2 kPa on regional fault systems Annual stress changes of ≤5 kPa in the principal orientation of the background stress field modulate low‐magnitude seismicity